Wilckodontics - A Novel Synergy in Time to Save Time - Sirisha K.; Srinivas M.; Ravinravindranath D.; Pratap Gowd (Journal of Clinical and Diagnostic Research, 2014)
The systematic search for improvements in orthodontic therapy is shared by several dental specalities especially periodontics. Rapid orthodontic treatment procedures are now focusing on performing Alveolar Corticotomies (ACS) shortly before the application of orthodontic forces. This method has been suggested to enhance tooth movement and, consequently, reduces orthodontic treatment time as a whole. Thus, this article attempts to review the historical perspective of these therapeutic approaches, discusses the biological reasons underlying its use, mentions its main indications and contraindications and its modifications.